2021
DOI: 10.3389/fphar.2021.743541
|View full text |Cite
|
Sign up to set email alerts
|

Bisbenzylisoquinoline Alkaloids of Cissampelos Sympodialis With in Vitro Antiviral Activity Against Zika Virus

Abstract: In search of new antiviral compounds against Zika virus we conducted a bioassay-guided fractionation of bisbenzyilisoquinoline alkaloids isolated from Cissampelos sympodialis (Menispermaceae), a medicinal plant species endemic to Brazil. Six subfractions were obtained from a tertiary alkaloidal fraction of the rhizomes (TAFrz) using preparative high-performance liquid chromatography. All the subfractions were tested against Zika virus-infected Vero cells as the cellular model to evaluate cytotoxicity and antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The alkaloids lycorine and cherylline, isolated from Crinum jagus , were active against ZIKV in Huh 7.5 cells (SI = 35.4 and SI >12.3, respectively) [ 99 ], along with warifteine, isolated from Cissampelos sympodialis , tested in ZIKV-infected Vero cells (SI = 68.3) [ 100 ].…”
Section: Nps With Potential Anti-zikv Activitymentioning
confidence: 99%
“…The alkaloids lycorine and cherylline, isolated from Crinum jagus , were active against ZIKV in Huh 7.5 cells (SI = 35.4 and SI >12.3, respectively) [ 99 ], along with warifteine, isolated from Cissampelos sympodialis , tested in ZIKV-infected Vero cells (SI = 68.3) [ 100 ].…”
Section: Nps With Potential Anti-zikv Activitymentioning
confidence: 99%
“…Silva and colleagues extracted a bisbenzylisoquinoline alkaloid, warifteine (24A), from the rhizomes of Cissampelos sympodialis , which proved to be an anti-DENV ( da Silva et al, 2021a ). Subsequently, they found that (24A) and methylwarifteine (25A) had strong effects against the Zika virus in vitro , and could be used as a pharmacophore or lead compounds to counteract Zika-virus infection ( da Silva et al, 2021b ). Zeng’s team identified that dehydrocheilanthifoline (26A) had anti-hepatitis B virus (HBV) activity in vitro , making it a promising drug candidate for the treatment of HBV infection ( Zeng et al, 2013 ).…”
Section: Alkaloidsmentioning
confidence: 99%